Structural evolution of ferromagnetic 3He multilayers adsorbed on exfoliated graphite - Antsygina, T.N.; Chishko, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
On the basis of our theoretical results describing two-dimensional spin-1/2 Heisenberg model in an external magnetic field we analyze and interpret known from literature experimental data on magnetization of pure 3He monolayers on graphite at ferromagnetic coverages. We clarify the experimentally observed temperature dependences for 2D 3He magnetization under magnetic fields of different magnitude. The cluster size effect in the temperature dependence of the magnetization is studied. We interpret the spin exchange variation in 2D multilayered 3He system during successive promotion of the second, third and fourth layers over first paramagnetic layer strongly coupled with graphite substrate.